Effect of frailty on the short-term functional outcome of elderly patients with traumatic brain injury - Yujing Gu; Huiqin Cui; Yang Gu; Xiaojiang Liu (Guoji laonian yixue zazhi)
[Objective] To investigate the effect of frailty on the short-term functional outcome of elderly patients with traumatic brain injury. [Methods] A retrospective analysis was conducted on 127 elderly patients with traumatic brain injury admitted to Hai’an People’s Hospital from April 2019 to April 2022.General information, demographics, clinical indicators and imaging results were collected.The clinical frailty scale that provides an assessment of the presence and severity of frailty was applied.The in-hospital mortality and neurological status at 3 months of onset were compared between the frail and non-frail groups.Multivariate logistic regression were used to clarify the factors affecting the prognosis of patients' neurological function, and clarify the predictive power of Glasgow coma scale and logistic regression model for neurological function prognosis through ROC curve analysis. [Results] Among the 127 elderly patients with traumatic brain injury, 48 cases had frailty.A total of 34 patients died during hospitalization, and 63 patients had poor neurological outcome at 3 months follow-up.Compared with the non-frailty group, the frailty group was older, had a higher mortality rate during hospitalization, and had a higher proportion of poor neurological prognosis at 3 months after onset (P<0.05).Multivariate logistics regression analysis shows that age >75 years old, higher Glasgow coma score and clinical frailty score ≥5 were independent risk factors for poor neurological prognosis in elderly patients with traumatic brain injury at 3 months onset.The results of the ROC curve indicated that the area under the curve of the Glasgow coma score predicting poor neurological prognosis in elderly patients with traumatic brain injury at 3 months after onset was 0.643 (95%CI:0.532-0.727), which was increased to 0.874 (95%CI:0.782-0.931) when indicators of patient age, Glasgow coma score and clinical frailty score were applied. [Conclusion] Elderly traumatic brain injury patients with frailty have higher mortality and unfavorable prognosis that deserves clinical attention.